Unfinished Business? Academic and Labor Market Profile of Adults With Substantial College Credits But No Degree. (September 2022) - Bird, Kelli A.; Castleman, Benjamin L.; Fischer, Brett; Skinner, Benjamin T.
Recent state policy efforts have focused on increasing attainment among adults with some college but no degree (SCND). Yet little is actually known about the SCND population. Using data from the Virginia Community College System (VCCS), we provide the first detailed profile on the academic, employment, and earnings trajectories of the SCND population and how these compare with VCCS graduates. We show that the share of SCND students who are academically ready to re-enroll and would benefit from doing so may be substantially lower than policy makers anticipate. Specifically, we estimate that few SCND students (approximately 3%) could fairly easily re-enroll in fields of study from which they could reasonably expect a sizable earnings premium from completing their degree.